Fermionic correlators on the holographic neutron star - Acito, Lucas (2025)
We investigate the fermionic perturbations of the asymptotically AdS background known as holographic neutron star, which represents a highly degenerate state of strongly coupled fermions on a sphere at finite temperature. We calculate the two-point correlator of a fermionic operator and obtain its scaling properties as we approach the critical region of the phase diagram.